Reliability of Thermal Energy Storage Technologies - Weishaupt, Daniel; Müller, Karsten (Chemie Ingenieur Technik, 2021)
Thermal energy storage is considered an important element of future energy systems. However, it is mandatory that the storage technologies work reliably. More complex systems are usually more prone to failure. As system size increases and functionalities can be separated, a more differentiated analysis is necessary. Large-scale applications often involve intrinsic redundancy because scale-up to some extent is realized through numbering-up. Therefore, failures of individual components do not cause total outage of the thermal energy storage, but only a certain loss in performance. A special feature of some thermochemical storage technologies is that separate parts of the whole system provide the functionalities of charging and discharging. Consequently, many failure modes do not cause a complete loss of functionality, but only of one of the two functionalities.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Dependability; Failure; Heat storage; Resilience